Effect of Breed and Holding Period on Egg Quality Characteristics of Chicken - Monira, K.N.; Salahuddin, M.; Miah, G. (International Journal of Poultry Science, 2003)
The external and internal qualities of 80 fresh eggs from each Barred Plymouth Rock (BPR), White Leg horn (WL), Rhode Island Red (RIR) and White Rock (WR) layers were ascertained in one, seven, fourteen and twenty-one days holding periods. Egg weight was highest in WLH (58.38 g), intermediate in BPR (56.3g) and RIR (55.95g) and lowest in WR (59.60g). Egg length was highest in WLH (5.91 cm), intermediate in BPR (5.86 cm) and RIR (5.71 cm) and lowest in WR (5.62 cm). Egg width was highest in WLH (4.21 cm), intermediate in BPR and WR (4.16 cm) and lowest in RIR (4.13 cm). Shape index was highest in WR (74.10), intermediate in RIR (72.32) and WLH (71.34) and lowest in BPR (71.14). Breaking strength was highest in WLH egg (3.38 kg/cm), intermediate in RIR (3.31 kg/cm) and BPR (2.61 kg/cm) and lowest in WR (2.19 kg/cm) egg. Albumen height of WR, WLH, BPR and RIR egg was 4.66, 4.33, 4.19 and 3.60 mm respectively. Haugh unit was highest in WR (58.68), intermediate in WLH (45.81) and BPR (54.20) and lowest in RIR (45.81). Shell thickness was highest in WLH and RIR (0.35 mm), intermediate in WR (0.32 mm) and lowest in BPR (0.31 mm). There were significant difference among the breeds and holding period for all the egg quality traits except egg width. Breed and holding period interactions were significant for egg length, shape index, albumen height and Haugh unit but not for other traits. The egg weight, egg length, egg width, albumen height and Haugh unit of all breeds were higher in fresh egg that means one days egg but breaking strength and shell thickness were higher in seven days holding period eggs than the other period eggs. The egg weight, egg length, egg width, breaking strength performance is superior in White Leghorn over other breeds. Shape index and albumen height is better in White Rock than other breeds.